2021
DOI: 10.3390/ijerph18179188
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Occupational Burnout: A Systematic Review

Abstract: We aimed to review occupational burnout predictors, considering their type, effect size and role (protective versus harmful), and the overall evidence of their importance. MEDLINE, PsycINFO, and Embase were searched from January 1990 to August 2018 for longitudinal studies examining any predictor of occupational burnout among workers. We arranged predictors in four families and 13 subfamilies of homogenous constructs. The plots of z-scores per predictor type enabled graphical discrimination of the effects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 100 publications
4
45
0
1
Order By: Relevance
“…High job demands and poor decision authority are risk factors for a number of ill-health outcomes. For example, in systematic reviews, high job demands [ 9 , 10 , 11 , 12 ] and poor decision authority [ 9 , 12 , 13 ] are associated with increased risks of common mental disorders, which are the most common diagnoses behind sickness absences in Sweden [ 14 ]. High demands and poor job control or decision authority are also directly associated with increased risks of sickness absence in general working populations [ 15 , 16 , 17 , 18 , 19 , 20 ], specifically within health and social care [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…High job demands and poor decision authority are risk factors for a number of ill-health outcomes. For example, in systematic reviews, high job demands [ 9 , 10 , 11 , 12 ] and poor decision authority [ 9 , 12 , 13 ] are associated with increased risks of common mental disorders, which are the most common diagnoses behind sickness absences in Sweden [ 14 ]. High demands and poor job control or decision authority are also directly associated with increased risks of sickness absence in general working populations [ 15 , 16 , 17 , 18 , 19 , 20 ], specifically within health and social care [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The material includes online information packages, videos, pre-recorded roleplays, animated scenarios showing case studies, short quizzes, reflection exercises, breathing and mindfulness exercises, and practical stress management exercises. Research shows that having coping strategies may prevent occupational burnout [ 16 ]. The Hub is designed to give tailored content to the construction sector, the healthcare sector, and the ICT sector with examples typically experienced within the sectors and presented in videos and animated scenarios by workers from each of the sectors.…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review of predictors for burnout, job demands, lack of job resources, lack of social support, social hindrance, poor organisational commitment, high work-family conflict, and poor communication may have harmful effects on occupational burnout [ 16 ]. Research has consistently shown that people in specific occupational sectors—construction and health—have mental health problems and an elevated risk of suicide, jointly representing up to 49% of male suicides and 26% of female suicides [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Workers who experience low pleasure and activation may experience occupational burnout, a state characterised by physical and emotional exhaustion and by disconnectedness. A recent meta-analysis by Shoman et al (2021) highlights excessive job demands and negative work attitudes as key predictors of occupational burnout. There is also evidence that workers from particular sectors (e.g., teachers) are more likely to experience burnout and that training courses and policies aimed at boosting workers’ internal resources and abilities to cope with work-related stress and emotional demands (adaptive coping strategies) may render them less susceptible to burnout ( Pishghadam et al, 2021 ; Shoman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%